2015
DOI: 10.1007/s10689-015-9834-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of APC I1307K and E1317Q polymorphisms with colorectal cancer among Egyptian subjects

Abstract: Colorectal cancer is a multifactorial disease that involves both environmental and genetic factors. The gene encoding adenomatous polyposis coli (APC) has been reported to be associated with colorectal cancer (CRC) risk in several ethnic populations. The aim of this work is to assess the association of the APC I1307K and E1317Q polymorphisms with CRC risk among Egyptian subjects. This study included 120 unrelated CRC Egyptian patients who were compared to 100 healthy controls from the same locality. For all su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…It is also present among Japanese patients and other Asian populations but it is rare elsewhere 50 . The index case has, in addition, a variant, Ile1307Lys in APC gene, previously described as a risk factor for breast, lung, urologic, pancreatic, and skin cancers 33,34 and has been associated with an increased risk of colorectal cancer among Ashkenazi Jewish, Croatian, and Egyptian patients [35][36][37] . This gene encodes a tumor suppressor protein that acts as an antagonist of the Wnt signaling pathway that regulates crucial aspects of cell fate determination, cell migration, cell polarity, neural patterning and organogenesis during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also present among Japanese patients and other Asian populations but it is rare elsewhere 50 . The index case has, in addition, a variant, Ile1307Lys in APC gene, previously described as a risk factor for breast, lung, urologic, pancreatic, and skin cancers 33,34 and has been associated with an increased risk of colorectal cancer among Ashkenazi Jewish, Croatian, and Egyptian patients [35][36][37] . This gene encodes a tumor suppressor protein that acts as an antagonist of the Wnt signaling pathway that regulates crucial aspects of cell fate determination, cell migration, cell polarity, neural patterning and organogenesis during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that it could predict the prevalence of breast, lung, urologic, pancreatic, and skin cancers 33,34 and it has been associated with an increased risk of colorectal cancer among Ashkenazi Jewish, Croatian, and Egyptian patients [35][36][37] .…”
Section: Screening For Rare and Pathogen Variantsmentioning
confidence: 99%
“…The same holds true for colorectal cancer, where there is little population-level data surrounding the prevalence of germline mutations in common cancer susceptibility genes. Germline mutations reported in the literature from African countries suggest that these variants are typically different from those found in HICs and the clinical significance of these mutations remains poorly characterised ( 7 , 21 23 ).…”
Section: Molecular Divergence In Cancer Aetiologymentioning
confidence: 99%
“…A specific germ-line missense mutation, involving transition of T to A at nucleotide 3920 of the APC gene causes the substitution of lysine for isoleucine at codon 1307 [135]. In a recent study, the APC I1307K variant has also been associated with an increased risk of CRC among Ashkenazi Jewish, Croatian, and Egyptian subjects [136142]. While studies indicate that I1307K substitution predisposes to colorectal cancer, it has also been shown to predict the prevalence of breast, lung, urologic, pancreatic, and skin cancers [143, 144].…”
Section: Polymorphic Variations In Apc and Fen1 Genes That May Affmentioning
confidence: 99%